2007
DOI: 10.1121/1.2713670
|View full text |Cite
|
Sign up to set email alerts
|

Boundary element method for the acoustic characterization of a machine in bounded noisy environment

Abstract: In this article, a boundary element method is used to recover free field conditions from noisy bounded space situations. The proposed approach is based on the Helmholtz integral formulation. The method requires the knowledge of double layer pressure fields on two parallel closed surfaces surrounding the source. First, the outgoing and ingoing pressure field are separated using Helmholtz integral. Then, the incident field scattered by the tested source is subtracted from the outgoing field to recover the pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…The boundary element method using a double layer [4] was proposed to overcome the restriction on the shapes of measurement surfaces. In order to overcome the problem of the truncation effect and wrap-around errors when the measurement aperture is not large enough in the classical NAH technique, the statistically optimized nearfield acoustical holography (SONAH) has been proposed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The boundary element method using a double layer [4] was proposed to overcome the restriction on the shapes of measurement surfaces. In order to overcome the problem of the truncation effect and wrap-around errors when the measurement aperture is not large enough in the classical NAH technique, the statistically optimized nearfield acoustical holography (SONAH) has been proposed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A methodology based on the Green's representation of the pressure field has been proposed by Langrenne et al [7] to extract the outgoing radiated component from the measured acoustic pressure generated by a machine in an enclosure. It could be well suited for the IBEM localisation of the most vibrating parts of a machine.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, it was shown that the room component of the total sound field, i.e. the sum of the incoming and scattering parts as in the usual terminology [18], can be approximated by radiation from a distribution of equivalent sources, monopoles in that case. Bi and Bolton's main concern was, however, to identify the free-space component of a source's radiation in a reverberant environment.…”
Section: Introductionmentioning
confidence: 99%